👤
Dariannimis
a fost răspuns

[(3+a:2):11+7]×5-9=41​

Răspuns :

Răspuns:

BUNĂ

Metoda mersului invers

41+9=50

50:5=10

ADICĂ

(3+A:2):11+7=10

(3+A:2):11=3

3+A:2=33

A:2=30

A=2×30

A=60

Sper că te-am ajutat !

Dallia

Răspuns:

=

Explicație pas cu pas:

[(3 + a : 2) : 11 + 7] x 5 - 9 = 41

[(3 + a : 2) : 11 + 7] x 5 = 41 + 9

[(3 + a : 2) : 11 + 7] x 5 = 50

[(3 + a : 2) : 11 + 7] = 50 : 5

[(3 + a : 2) : 11 + 7] = 10

(3 + a : 2) : 11 = 10 - 7

(3 + a : 2) : 11 = 3

3 + a : 2 = 3 x 11

3 + a : 2 = 33

a : 2 = 33 - 3

a : 2 = 30

a = 30 x 2

a = 60